Human resources for industrial development : some aspects of policy and planning - International Labour Office (Geneva : International Labour Office, 1967)
This volume is a collection of papers prepared by the International Labour Office for an international symposium planned by the newly established United Nations Industrial Development Organisation to follow the series of regional symposia held in 1966. The purpose of the papers is to identify some of major manpower and social problems encountered by developing countries in the process of industrial development, and to discuss action that needs to be taken both at national and at international levels if these problems are to be solved.
Includes bibliographical footnotes.
rpm 28/03/2018
Loans
Keywords: Manpower policy; Industrialization; Labor supply